Mental and physical health correlates of discrimination against people who inject drugs: A systematic review - Couto E Cruz, C.; Salom, C.; Maravilla, J.; Alati, Rosa (Alcohol Research Documentation, Inc Rutgers, 2018)
© 2018, Alcohol Research Documentation Inc. All rights reserved. Objective: The perception that people who use illicit drugs are deviant has contributed to the stigmatization of this population. The primary aim of this review is to examine the links among injection-related discrimination, mental health, physical health, and quality of life in people who inject drugs. We also identify settings, perpetrators of discrimination, and coping strategies developed by people who inject drugs to deal with the issue. Method: Online databases MEDLINE (PubMed), EMBASE, CINAHL (EbscoHost), and PsycINFO (APA PsycNET) were searched for articles focusing on injection-related discrimination against people who inject drugs. Findings were compared for consistency. Qualitative and quantitative articles were evaluated separately. Results: Eleven articles were included in the final review. Several links between discrimination and negative health outcomes were identified. Discrimination was associated with engagement in risky injecting behavior as well as psychological distress. The perpetrators of discrimination against people who inject drugs included general community members and service providers. Attempts to hide addiction was the main strategy used to cope with discrimination. Conclusions: Injection-related discrimination was associated with higher psychological distress levels, unhealthy behaviors, and low quality of life in people who inject drugs. By addressing the stigma of deviance, discrimination and associated negative health outcomes may be reduced.